En queer introduktion till texten Gränslösa hundar: Om queerteori, performativitet och subversiva repetitioner i skönlitterära, kritiska och vetenskapliga texter - Hallgren, Hanna (Kvinder, Køn & Forskning, 2013)
This article is a queer introduction to the genre transboundary text Gränslösa hundar written by the poet Jenny Tunedal and Hanna Hallgren in 2007. The article quotes and discuss central parts of Gränslösa hundar, and makes overall reflections on queer theory, performativity and subversive repetitions in fictional, critical and scientific texts. The article uses writing as a method of inquiry and devotes itself to philosophical traditions, which do not make harsh distinctions between conceptual and somatic knowledge. It also believes in a poetic truth. The academic fields that this article inscribes itself into are transversally joined – it cuts across queer studies, gender studies, reflexive academic writing, creative writing and artistic research.